2022
DOI: 10.1101/2022.12.25.521651
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Innovative, rapid, high-throughput method for drug repurposing in a pandemic –a case study of SARS-CoV-2 and COVID-19

Abstract: Several efforts to repurpose drugs for COVID-19 treatment have largely either failed to identify a suitable agent or agents identified did not translate to clinical use; either because of demonstrated lack of clinical efficacy in trials, inappropriate dose requirements and probably use of inappropriate pre-clinical laboratory surrogates of effectiveness. In this study, we used an innovative algorithm, that incorporates dissemination and implementation considerations, to identify potential drugs for COVID-19 us… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 87 publications
0
10
0
Order By: Relevance
“…Folic acid also significantly inhibits SARS-CoV-2 Papain like protease and at concentrations and IC 50 that are also achievable at routine therapeutic doses. Indeed, previous molecular docking studies by our group 4 and others 24 suggest Folic acid as potential therapeutic in COVID-19. Wet laboratory studies further suggest that Folic acid inhibits SARS-COV-2 nucleocapsid protein 25 and inhibits cell invasion by SARS-CoV-2 by methylating ACE2 26 .…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Folic acid also significantly inhibits SARS-CoV-2 Papain like protease and at concentrations and IC 50 that are also achievable at routine therapeutic doses. Indeed, previous molecular docking studies by our group 4 and others 24 suggest Folic acid as potential therapeutic in COVID-19. Wet laboratory studies further suggest that Folic acid inhibits SARS-COV-2 nucleocapsid protein 25 and inhibits cell invasion by SARS-CoV-2 by methylating ACE2 26 .…”
Section: Discussionmentioning
confidence: 89%
“…This study was conducted as standalone evaluation of the effect of drugs previously identified by in silico screening 4 as potential therapeutics for SARS-CoV-2 infection and COVID-19. Although effect on SARS-CoV-2 induced CPE in Vero cells, SARS-CoV-2 Main protease (M PRO ) and Papain-like protease (PP) were evaluated, these were not considered necessarily linked (mechanistic) because the initial in silico selection was based on predicted activity at 11 independent targets 4 , any combination of which may be related to observed inhibition of CPE. It is interesting that Nirmatrelvir-ritonavir combination(Paxlovid) 17,18 , the current forerunner in COVID-19 therapeutics is an M PRO inhibitor and it is accepted that its efficacy is related to this inhibition 19 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations